x = 7
First, subtract 3x from each side of the equation. Then, divide each side of the equation by 7 .
so -x = 56 making x = -56.
3X+70-7*18=0 3X+70-126=0 3X-56=0 3X=56 x=56/3 or 18.6667
X= 20.6666666666667
x = 7
First, subtract 3x from each side of the equation. Then, divide each side of the equation by 7 .
so -x = 56 making x = -56.
3X+70-7*18=0 3X+70-126=0 3X-56=0 3X=56 x=56/3 or 18.6667
X= 20.6666666666667
3x + 7 = 56 - 4xAdd 4x to each side of the equation:7x + 7 = 56Subtract 7 from each side:7x = 49Divide each side by 7:x = 7
112
x=-24. x+56=8-x therefore x+56-8=x and x+x+56-8=0. to make things easier, 2x+48=0 and you get 2x=-48. divide -48 by 2 and x=-24.
2x-10+3x-10 = 90 5x = 110 x = 22 degrees angles are 34 and 56 degrees
1 + 2 + 56 = 59
56 plus 1 equals 57. == ==
(7 x 8) + 3 - (2 x 8)= 56 + 3 - 16= 43